Comparative study of butorphanol and fentanyl in attenuation of haemodynamic responses in laparoscopic cholecystectomy - Balwinder Kaur Rekhi; Priyanka Mehta; Sandeep Kaur Sidhu (GMC Patiala Journal of Research and Medical Education, 2019)
Numerous attempts have been made in the past to attenuate the haemodynamic responses occurring during laparoscopic cholecystectomy. The present study compared the effect of two opioids namely Butorphanol and Fentanyl in obtundation of haemodynamic responses in laparoscopic cholecystectomy in terms of Heart rate, BP (SBP, DBP and MAP). Materials And Methods : This was a randomised study comparing opioid drugs- fentanyl and butorphanol. It was carried out on 50 patients of either sex aged 18 - 60 years scheduled for elective laparoscopic cholecystectomy under GA. Subjects were enrolled into two groups- Group I (n= 25) patients received inj. butorphanol 25 mcg/kg IV, Group II (n= 25) received inj. fentanyl 2 mcg/kg IV before the induction. Result : At the time of extubation, mean MAP in Group I and II was 99.88 and 95.32 was respectively. This difference is highly significant when compared statistically (p value is 0.005). Conclusion: With this study, we conclude that the administration of intravenous fentanyl five minutes prior to induction of anaesthesia helps in better obtundation of haemodynamic responses to laparoscopic cholecystectomy than butorphanol.